Network Security System Analysis Using Access Control List (ACL) - Oris Krianto Sulaiman; Darjat Saripurna (IJISTECH (International Journal of Information System and Technology), 2021)
Communication using internet media is a mandatory requirement today to carry out various activities. Communication through the internet will pass through public access, where many people use public access. When communication is in progress, many things can happen before the message reaches its destination. One of them is the occurrence of hacking attempts from irresponsible parties. Therefore, it is necessary to secure the communication process, and many network security methods can be used to secure the communication process in the internet network. Access Control List or ACL is one method that can be used to secure communication in the network. ACL makes it easy to block specific devices and ports to prevent network communication. The results of the ACL implementation have the impact of avoiding access so that not all devices or protocols can access certain communications, thereby increasing network security in the process.